Vineyard diseases detection: a case study on the influence of weather instruments' calibration and positioning. (15th September 2017) - Sanna, Francesca; Calvo, Angela; Deboli, Roberto; Merlone, Andrea
ABSTRACT: Weather‐monitoring instruments installed on hill and mountain agricultural sites are often forced into non‐ideal positioning due to slopes, tree proximity and other obstacles such as rivers and rocks that primarily affect relative humidity, temperature and solar radiation. Moreover, data from these weather stations do not take into account the measurement uncertainties related to these influences. The aim of this study is to investigate weather instruments' calibration and positioning in a vineyard located in the Monferrato region in northwestern Italy. Meteorological data from two weather stations were analysed metrologically in terms of the evaluation of calibration uncertainty and traceability to the International System of Units (SI), and using a statistical test, with the purpose of evaluating primarily the effect of the sensors' calibration and positioning on sloping hills. To understand these influences better, and in order to improve vineyard disease predictions reducing the use of chemicals in agriculture, the data recorded from the weather stations were included with the calibration uncertainties and used as inputs in an epidemiological forecasting model. The inclusion of the calibration uncertainties and positioning contribution affected disease prediction by up to five days; this can be explained by the effect of the tree canopy's spatial arrangement, which tends to alter the vineyard's microclimate. Abstract : Transportable calibration chamber "Earth Dynamics Investigation Experiment (EDIE)": (a) project drawing, (b) external configuration with thermostat and (c) internal configuration.